Monitoring Toddler Development Based on Indonesia Health Survey (SKI) 2023 - Russiska, Russiska; Cahyati, Widya Hary (Journal of Creativity Student, 2025)
Background: Monitoring the development of toddlers is an essential aspect of the early detection of child growth and development problems. However, its implementation in Indonesia still faces various challenges, such as low parental awareness and limited access to health services. This study aims to identify factors related to monitoring the development of toddlers based on data from the 2023 Indonesian Health Survey (SKI).  Method: This study uses a quantitative method with a cross-sectional design involving all children aged 0-6 years in Indonesia. Data were collected through standardized questionnaires and structured interviews, then analyzed using simple linear regression to measure the relationship between socioeconomic factors, ownership, and utilization of KIA books, as well as access to health centers for child development monitoring. Result: The results showed that the most dominant factor in supporting development monitoring was the ownership and utilization of KIA books, with a powerful and significant correlation (R=0.781 and R=0.788). Easy access to health centers also has a considerable influence (R=0.681). In contrast, economic status has a lower relationship and is not statistically significant in most categories. Conclusion: These findings highlight the importance of increasing parental awareness of using KIA books and optimizing access to health services to support better child development monitoring.